War Ethics and War Morality: An Introduction - Babić, Jovan (Conatus - Journal of Philosophy, 2023)
War ethics might sound as impossible combination of words – how justify what seems to be unjustifiable? War is prima facie unjustifiable. However, wars are a fact of human reality, and those among us who are unfortunate to live in times of war – in a way it is all of us – would know that the reality is not just a possibility, that prima facie designation does not help in answering what must be done, that unjustifiability does not imply impossibility. We must understand to be able to explain, and to explain to have a valid evaluation, especially when what is happening is important and with far-reaching consequences. Wars are such phenomena. We live amid such phenomena, and we need to understand not only their tragic and often cataclysmic nature, but also their meaning, their structure and logic of their functioning. We should understand that war is not something that happens only to others, nor that it is the matter of the past. In the present volume we have thirty-three essays examining war from many angles, sometimes from the opposite standpoints, exploring some of the most intriguing issues of warfare in times characterized by radical changes in the world in turmoil. The contributions in present volume give an overview of the world’s thinking about war. The volume is certainly incomplete and unfinished, but it gives a lot of thought-provoking incentives to think about the most important aspects of warfare and its broad phenomenology.